Outer membrane proteins of Fusobacterium necrophorum and their role in adhesion to bovine cells - Kumar, Amit (Kansas State University, 2013)
Fusobacterium necrophorum is a Gram-negative, anaerobic, and rod-shaped to pleomorphic bacterium. It is frequently associated with necrotic infections of animals and humans. It is a major bovine pathogen and causes hepatic abscesses, foot rot, and necrotic laryngitis (calf-diphtheria). Liver abscesses in feedlot cattle and foot rot in beef and dairy cattle are of significant economic importance to the cattle industry. Fusobacterium necrophorum is classified into two subspecies, subsp. necrophorum and subsp. funduliforme. The subsp. necrophorum is more virulent and isolated more frequently from bovine hepatic abscesses than subsp. funduliforme. Outer membrane proteins (OMPs) of Gram-negative bacteria play an important role in their adhesion to host eukaryotic cells and hence, help in the establishment of infection and disease. Our objectives were to characterize OMPs of the two subspecies of F. necrophorum and assess their role in adhesion to bovine cells. Electrophoretic separation of extracted OMPs of subsp. necrophorum showed a total of 19 bands. Four bands of 38, 40, 60 and 74 kDa were more prominent than others. The OMPs of subsp. funduliforme showed a total of 20 proteins bands, of which, five were prominent (37.5, 58, 70, 140 and 150 kDa). The 40 kDa band was prominent in subsp. necrophorum while 37.5 kDa band was prominent in subsp. funduliforme. The human strains of F. necrophorum subsp. funduliforme had more heterogeneous banding patterns than the bovine strains of subsp. funduliforme. The role of OMPs in adhesion was studied using bovine endothelial cell line (EJG cells). A significant decrease in the attachment of subsp. necrophorum and subsp. funduliforme to bovine endothelial cell line (EJG cells) was observed when the cell line was preincubated with the OMPs of each subspecies. Treatment of the bacterial cells with trypsin also decreased their binding. In addition, when each subspecies was incubated with the polyclonal antibody produced against their OMPs before adding them to endothelial cells, there was a significant reduction in the bacterial attachment and the inhibition was subspecies specific. A 40 kDa OMP of subsp. necrophorum was identified that binds to the bovine endothelial cells with high affinity. The protein when preincubated with the endothelial cells, lead to a significant decrease in the bacterial binding to the endothelial cells. The N-terminal sequencing of the protein indicated similarity to FomA, an outer membrane protein of Fusobacterium nucleatum, an oral pathogen of humans. In summary, OMPs of F. necrophorum subsp. necrophorum and subsp. funduliforme differ from each other and they play a significant role in binding to bovine endothelial cells. We identified a 40 kDa OMP in subsp. necrophorum that binds to the bovine endothelial cells with high affinity and have a potential role as adhesin.
Keywords: Fusobacterium necrophorum; Adhesins; Outer membrane proteins; Liver abscesses; Microbiology (0410); Molecular Biology (0307)